Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.24349/acarologia/20204360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollen of different plant species on the oviposition of two phytoseiid mites (Acari: Phytoseiidae) commonly found in citrus orchards in the Brazilian Amazonia

Abstract: The suitability of the use of pollen to foster the control of citrus pests by facilitating the maintenance of predatory mites in the area has been extensively studied. The aim of this study was to evaluate the effect of pollen of 13 plant species commonly found in Manaus region (Brazilian Amazonia) on the oviposition of Amblyseius aerialis and Iphiseiodes zuluagai, phytoseiid species abundant in citrus orchards in that region. The study was conducted under laboratory conditions, using mostly pollen grains rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Among angiosperm species, pollen grain diameter ranges from less than 10 μm (e.g., in forget-me-not, Myosotis) to over 100 μm (in some species like cotton or cucumber) (Hao et al 2020). They are categorised as very small (< 10 μm), small (10−25 μm), medium (25−50 μm), large (50−100 μm), very large (100−200 μm), or giant (>200 μm) (Ferreira et al 2020). So, considering the maximum effective gape of the three species herein they could only grasp small to medium grains like those of the common sunflower (Helianthus annuus) found in UK gardens (and thus in beehives), coriander, dill, and wild roses for instance (but not Hibiscus pollen, nor pollen from wheat (Golan and Pringle 2017)).…”
Section: Span Of Moveable Digitmentioning
confidence: 99%
“…Among angiosperm species, pollen grain diameter ranges from less than 10 μm (e.g., in forget-me-not, Myosotis) to over 100 μm (in some species like cotton or cucumber) (Hao et al 2020). They are categorised as very small (< 10 μm), small (10−25 μm), medium (25−50 μm), large (50−100 μm), very large (100−200 μm), or giant (>200 μm) (Ferreira et al 2020). So, considering the maximum effective gape of the three species herein they could only grasp small to medium grains like those of the common sunflower (Helianthus annuus) found in UK gardens (and thus in beehives), coriander, dill, and wild roses for instance (but not Hibiscus pollen, nor pollen from wheat (Golan and Pringle 2017)).…”
Section: Span Of Moveable Digitmentioning
confidence: 99%
“…Sternal shield smooth, lightly sclerotized with three pairs of setae (ST1, ST2, ST3), two pairs of poroids (pst1 and pst2). Distance (ST1-ST3) 59 (58)(59)(60)(61), width (ST2-ST2) 61 (60)(61)(62)(63). Metasternal setae ST4 and a pair of pores (pst3) on metasternal shields.…”
Section: Familymentioning
confidence: 99%
“…Amblyseius aerialis is also a generalist predator with Type-III feeding habit [60]. It was first collected feeding on six-spotted spider mite, Eotetranychus sexmaculatus, and has since been found in citrus orchards from Guadeloupe, Dominican Republic, Florida, and Brazil [51,54,61,62]. Studies showed that it can feed and reproduce on T. urticae [63,64].…”
Section: Implications For Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Весьма распространенной разновидностью подкормок хищных клещей в теплицах является пыльца, которая рекомендована для поддержания в основном тех видов, которые могут завершать развитие и откладывать яйца, питаясь исключительно данным видом корма (Onzo et al, 2005;Goleva, Zebitz, 2013;Adar et al, 2014;Ferreira et al, 2020;Pascua et al, 2020). В присутствии пыльцы эффективность колонизации хищников повышалась в борьбе с разными видами вредителей: паутинными клещами (Saber, 2013;Duarte et al, 2015;Pijnakker et al, 2016), трипсами (Ramakers, 1990; и белокрылкой (Nomikou et al, 2010).…”
Section: сезонная колонизация и наводняющие выпускиunclassified